Kinematics and Force Analysis of Screw Pair Steel Ball Planetary Transmission Mechanism - Wang Hongxin (Jixie chuandong)
This paper introduces the construction composition and transmission principle of the screw pair steel ball planetary transmission mechanism with a coaxal input and output axes,calculates their transmission ratio function,gives the geometrical conditions of loading steel balls even distributed in space,presents the construction parameter constraint equation of the internal and external screw surfaces under the conditions of the steel ball loaded through three points,and sets up the calculation method of counteraction forces on bearings under space forces action.